1995
DOI: 10.1103/physrevlett.75.272
|View full text |Cite
|
Sign up to set email alerts
|

Branching of Critical Conditions for Si(111)-(7×7) Oxidation

Abstract: From kinetic measurements by optical second harmonic generation of 02 interaction with Si(111)-(7 X 7) at temperatures between 610 and 735 'C and pressures from 10 9 to 10 6 tort, we determine the boundaries for oxide nucleation and for quasiequilibrium between surface phases of oxide and silicon. The distinction between these boundaries rejects the influence of the kinetic parameters of the surface reactions on the critical conditions. At T~700 C, the oxide nucleation requires oxygen pressure well above that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Rapid Thermal Processing and beyond: Applications in Semiconductor Processing pressure range between 10 -7 and 10 -4 mbar. Shklyaev et al [57] [58] have shown the influence of oxide quality, i. e. the oxidation growth conditions on the desorption process, which is based on the dissociation of SiO 2 to SiO(g) the following chemical reaction:…”
Section: Thermal Desorption and Oxidationmentioning
confidence: 99%
“…Rapid Thermal Processing and beyond: Applications in Semiconductor Processing pressure range between 10 -7 and 10 -4 mbar. Shklyaev et al [57] [58] have shown the influence of oxide quality, i. e. the oxidation growth conditions on the desorption process, which is based on the dissociation of SiO 2 to SiO(g) the following chemical reaction:…”
Section: Thermal Desorption and Oxidationmentioning
confidence: 99%